Evaluating potential sugar food sources from the olive grove agroecosystems for Prays oleae parasitoid Chelonus elaeaphilus. Issue 5 (4th May 2017) - Nave, Anabela; Gonçalves, Fátima; Nunes, Fernando M.; Campos, Mercedes; Torres, Laura
ABSTRACT: Chelonus elaeaphilus Silvestri (Hymenoptera: Braconidae) is a host-specific parasitoid of the olive moth, Prays oleae (Bernard), that can cause parasitism rates of up to 80% in Mediterranean olive groves. A laboratory study was carried out to assess the potential of sugars provided by wild plant species in olive grove agroecosystem to enhance the fitness of C. elaeaphilus . Insects were reared in a climate-controlled chamber at 25 ± 2°C, 60 ± 5% relative humidity (RH) with a photoperiod of 16:8 (L:D) h. Five naturally occurring wild plant nectar sugars (sucrose, fructose, glucose, maltose and mannose) were tested for their effect on insect longevity. The nectar sugar content of sucrose, fructose and glucose in 12 selected olive grove agroecosystem plant species was analysed and categorised on the basis of sugar ratios. Female insect longevity was increased when they were fed on both sucrose and glucose compared to either maltose or fructose, suggesting that sucrose-dominant nectars would beneﬁt this parasitoid. Sucrose was predominant in the nectar of five of the studied plant species ( Silene gallica, Borago officinalis, Echium plantagineum, Lavandula stoechas and Lonicera hispânica ). The results are discussed in terms of potential enhancement of the biological control of P. oleae .